Material Strengthening of Muhadasah Through Short Video in Learning Arabic for Islamic Religious Education Students at Tgk. Chik Pantekulu Islamic College Banda Aceh - Sofia, Ana; Azmy, Khairul; Marzuki, Marzuki (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
Assignments are crucially important in learning Arabic. This research aims to describe the assignment model in Arabic language learning. Mastery of Arabic is usually only synonymous with mastery of qawaid or grammar, even though mastery of Arabic certainly requires mastering the four existing maharah or competencies, namely istima' (hearing), kalam (speaking), qiraah (reading) and kitabah (writing). Thus, it is appropriate that in learning Arabic, especially at the tertiary level, efforts should be made so that students master all language competencies. This research is a qualitative descriptive study that describes the results of the application of an assignment model in Arabic language learning. This research raises an assignment model applied in Arabic language learning at STAI (Islamic College) Tgk Chik Pante Kulu, namely short video assignments. This research data collection used interviews, observation, and documentation. The data sources used in this research were one Arabic language lecturer and three students who took Arabic language courses at STAI Tgk Chik Pante Kulu. This short video assignment can improve students' ability to master Arabic, especially in muhadatsah. As evidenced by the results of daily observations by researchers, there is an increase in ability from the initial test results compared to the results after the short video assignment. Hopefully, this assignment model can be applied in Arabic language learning to improve students' mastery of Arabic.Pemberian tugas memiliki peran yang sangat penting dalam pembelajaran bahasa Arab. Penelitian ini bertujuan untuk mendeskripsikan model pemberian tugas dalam pembelajaran bahasa Arab. Penguasaan bahasa Arab biasanya hanya diidentikkan dengan penguasaan qawaid atau tata bahasa, padahal penguasaan bahasa Arab tentunya memerlukan penguasaan empat maharah atau kompetensi yang ada, yaitu istima' (mendengar), kalam (berbicara), qiraah (membaca), dan kitabah (menulis). Oleh karena itu, sudah sepatutnya dalam pembelajaran bahasa Arab, khususnya di tingkat perguruan tinggi, dilakukan upaya agar mahasiswa dapat menguasai seluruh kompetensi berbahasa tersebut. Penelitian ini merupakan studi deskriptif kualitatif yang menggambarkan hasil penerapan model pemberian tugas dalam pembelajaran bahasa Arab. Penelitian ini mengangkat model pemberian tugas yang diterapkan dalam pembelajaran bahasa Arab di STAI (Sekolah Tinggi Agama Islam) Tgk Chik Pante Kulu, yaitu tugas berupa video pendek. Pengumpulan data penelitian ini dilakukan melalui wawancara, observasi, dan dokumentasi. Sumber data yang digunakan dalam penelitian ini adalah satu orang dosen bahasa Arab dan tiga mahasiswa yang mengikuti mata kuliah bahasa Arab di STAI Tgk Chik Pante Kulu. Tugas video pendek ini dapat meningkatkan kemampuan mahasiswa dalam menguasai bahasa Arab, khususnya pada aspek muhadatsah. Hal ini dibuktikan dengan hasil observasi harian oleh peneliti yang menunjukkan adanya peningkatan kemampuan dari hasil tes awal dibandingkan dengan hasil setelah pemberian tugas video pendek dilakukan. Semoga model pemberian tugas ini dapat diterapkan dalam pembelajaran bahasa Arab untuk meningkatkan penguasaan bahasa Arab mahasiswa